Pengembangan Video Tutorial Pembelajaran Basketball Dribbling - Muhammad Ali; Ilham Ilham; David Iqroni (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Physical and health education is carried out as part of an organized and continuous education process to acquire knowledge, personality, skills, health, and physical fitness. In this education, three domains must be achieved, such as cognitive, affective, and psychomotor. Of the three domains, the dominant one is the psychomotor domain because many subjects are directly related to motion values, such as movement abilities and skills. One of the compulsory subjects in the sports coaching study program, the Health Sports Education Study Program, Universitas Jambi, is basketball. Science and technology (IPTEK) is a term we often hear in everyday life. The development of society in all areas of life is inseparable from the existence of science and technology. In general, there is an assumption that the mastery and application of science and technology will guarantee the progress of society. This research is research and development. Research and development is a research method used to produce particular products and test the effectiveness of these products. In this case, research and development were carried out to obtain a video tutorial for learning basketball dribbling in the Health Sports Education Study Program, Universitas Jambi. This research and development were carried out based on the study that video tutorials for teaching basketball dribbling in the Health Sports Education Study Program at Universitas Jambi were not available. The research results showed that a video tutorial on basketball dribbling was arranged for the Health Sports Education Study Program, at Universitas Jambi. With the feasibility level based on the assessment of material experts, a percentage of 90% is included in the very feasible category, and the media expert's assessment is obtained with a percentage of 90%, including the very feasible category. The trial results obtained a percentage of 72% including the feasible category.